G-CSF and G-CSFR Modulate CD4 and CD8 T Cell Responses to Promote Colon Tumor Growth and Are Potential Therapeutic Targets - Karagiannidis, Ioannis; Jerman, Stephanie J.; Jacenik, Damian; Phinney, Brandon B.; Yao, Ruoxin; Prossnitz, Eric R.; Beswick, Ellen J. (Frontiers in Immunology, 2020)
Cytokines are known to shape the tumor microenvironment and although progress has been made in understanding their role in carcinogenesis, much remains to learn regarding their role in tumor growth and progression. We have identified granulocyte colony-stimulating factor (G-CSF) as one such cytokine, showing that G-CSF is linked with metastasis in human gastrointestinal tumors and neutralizing G-CSF in a mouse model of colitis-associated cancer is protective. Here, we set out to identify the role of G-CSF and its receptor, G-CSFR, in CD4+ and CD8+ T cell responses in the tumor microenvironment. MC38 colon cancer cells were injected into WT, G-CSFR−/− mice, or Rag2−/− mice. Flow cytometry, Real Time PCR and Multiplex cytokine array analysis were used for in vitro T cell phenotype analysis. Adoptive transfer of WT or G-CSFR−/− CD4+ of CD8+ T cells were performed. Mouse tumor size, cytokine expression, T cell phenotype, and cytotoxic activity were analyzed. We established that in G-CSFR−/− mice, tumor growth of MC38 colon cancer cells is significantly decreased. T cell phenotype and cytokine production were also altered, as both in vitro and in vivo approaches revealed that the G-CSF/G-CSFR stimulate IL-10-producing, FoxP3-expressing CD4+ and CD8+ T cells, whereas G-CSFR−/− T cells exhibit increased IFNγ and IL-17A production, leading to increased cytotoxic activity in the tumor microenvironment. Furthermore, peritumoral injection of recombinant IFNγ or IL-17A inhibited colon and pancreas tumor growth compared to controls. Taken together, our data reveal an unknown mechanism by which G-CSF, through its receptor G-CSFR, promotes an inhibitory Treg phenotype that limits tumor immune responses and furthermore suggest that targeting this cytokine/receptor axis could represent a novel therapeutic approach for gastrointestinal, and likely other tumors with high expression of these factors.